Rapidly progressive antineutrophil cytoplasm antibodies associated with pulmonary-renal syndrome in a 10-year-old girl - Blanco Filho, Fermin; Ernesto, Luci Carla; Rosa, Mônica Assis; Stuginski, Luis Antônio; Zlochevsky, Eliana Regina; Blanco, Fernando (São Paulo Medical Journal, 2001)
CONTEXT: The term pulmonary-renal syndrome has been used frequently to describe the clinical manifestations of a great number of diseases in which pulmonary hemorrhage and glomerulonephritis coexist. The classic example of this type of vasculitis is Goodpasture´s syndrome, a term used to describe the association of pulmonary hemorrhage, glomerulonephritis and the presence of circulating antiglomerular basement membrane antibodies (anti-GBM). Among the several types of systemic vasculitides that can present clinical manifestations of the pulmonary-renal syndrome, we focus the discussion on two types more frequently associated with antineutrophil cytoplasm antibodies (ANCA), microscopic polyangiitis and Wegener´s granulomatosis, concerning a 10 year old girl with clinical signs and symptoms of pulmonary-renal syndrome, with positive ANCA and rapidly progressive evolution. CASE REPORT: We describe the case of a 10-year-old girl referred to our hospital for evaluation of profound anemia detected in a primary health center. Five days before entry she had experienced malaise, pallor and began to cough up blood-tinged sputum that was at first attributed to dental bleeding. She was admitted to the infirmary with hemoglobin = 4 mg/dL, hematocrit = 14%, platelets = 260,000, white blood cells = 8300, 74% segmented, 4% eosinophils, 19% lymphocytes and 3% monocytes. Radiographs of the chest revealed bilateral diffuse interstitial alveolar infiltrates. There was progressive worsening of cough and respiratory distress during the admission day, when she began to cough up large quantities of blood and hematuria was noted. There was rapid and progressive loss of renal function and massive lung hemorrhage. The antineutrophil cytoplasm antibody (ANCA) test with antigen specificity for myeloperoxidase (anti-MPO) was positive and the circulating anti-GBM showed an indeterminate result.